Presence of zoonotic agents in engorged ticks and hedgehog faeces from Erinaceus europaeus in (sub) urban areas - Krawczyk, Aleksandra I; van Leeuwen, Arieke Docters; Jacobs-Reitsma, Wilma; Wijnands, Lucas M; Bouw, El; Jahfari, Setareh; van Hoek, Angela H A M; van der Giessen, Joke W B; Roelfsema, Jeroen H; Kroes, Michiel; Kleve, Jenny; Dullemont, Yolanda; et al. (Parasites & vectors, 2015)
Background European hedgehogs ( Erinaceus europaeus ) are hosts for Ixodes hexagonus and I. ricinus ticks, which are vectors for zoonotic microorganisms. In addition, hedgehogs may carry several enteric zoonoses as well. It is unclear to what extent a presence of pathogens in hedgehogs poses a risk to public health, as information on the presence of zoonotic agents in hedgehogs in urban areas is relatively scarce. Methods Engorged ticks and hedgehog faeces were collected from rehabilitating hedgehogs. Ticks were screened individually for presence of Borrelia burgdorferi sensu lato, B. miyamotoi , Anaplasma phagocytophilum , and Candidatus Neoehrlichia mikurensis using PCR-based assays. Faecal samples were screened for presence of Campylobacter, Salmonella , Giardia, Cryptosporidium , and extended-spectrum cephalosporin-resistant- Escherichia coli (ESC)-resistant E. coli , using both culture-based and PCR-based methods. Results Anaplasma phagocytophilum and Borrelia genospecies B. afzelii , B. spielmanii , B. garinii , and B. burgdorferi sensu stricto were detected in both I. hexagonus and I. ricinus ticks. Despite their widespread distribution in the Netherlands, B. miyamotoi and Candidatus N. mikurensis were not detected in collected ticks. Analysis of hedgehog faecal samples revealed the presence of Salmonella enterica subspecies enterica and Campylobacter jejuni . In addition, ESC-resistant E. coli were observed in high prevalence in faecal samples, but no Shiga-toxin producing -E.coli were detected. Finally, potentially zoonotic protozoan parasites were observed in hedgehog faecal samples as well, including Giardia duodenalis assemblage A, Cryptosporidium parvum subtypes IIaA17G1R1 and IIcA5G3, and C. hominis subtype IbA10G2. Conclusions European hedgehogs in (sub)urban areas harbor a number of zoonotic agents, and therefore may contribute to the spread and transmission of zoonotic diseases. The relatively high prevalence of B. burgdorferi s.l. and A. phagocytophilum in engorged ticks, suggests that hedgehogs contribute to their enzootic cycles in (sub)urban areas. To what extent can hedgehogs maintain the enteric zoonotic agents in natural cycles, and the role of (spill-back from) humans remains to be investigated.